Resilience in the face of rejection: coping strategies of reapplicants to a clinical psychology master’s programme - Antletse Phiriepa; Frans K. Matlakala; Curwyn Mapaling (Discover Social Science and Health)
Abstract Introduction The journey to becoming a clinical psychologist in South Africa is long, competitive, and emotionally demanding. Unsuccessful attempts to gain entry into the master’s programme more often than not lead many to experience psychological distress. Method A qualitative case study design was used, involving in-depth interviews with seven participants aged 24–30 who had applied to various universities. Data were collected via Microsoft Teams and analysed using reflexive thematic analysis. Co-coding was employed to enhance the credibility and rigour of the analysis. Results Participants experienced a range of negative emotional responses, including anxiety, anger, frustration, symptoms of depression, and diminished self-esteem. These emotional impacts were compounded by a sense of stagnation in their career trajectories. Nonetheless, participants demonstrated resilience by engaging in adaptive coping strategies such as cognitive reappraisal, seeking social support, pursuing self-development, and refining their applications in a problem-focused manner. Conclusion Despite enduring a significant emotional distress from repeated rejection, some of the applicants have employed adaptive coping strategies to sustain their resilience. The study calls for more transparent and supportive admissions process to better assist aspiring clinical psychology students.